The Embodiment of the Elements of Personal Psychological Theory of the Scientist Adler for the novel Khaj Al-Berlin by the novelist Hassan Ibrahim - Shvan Qasim Hasan; Dawlat Mohammed Ahmed (QALAAI ZANIST JOURNAL, 2024)
The novel, Khaj Al-Berlini by Hassan Ibrahim, is considered the most important literary genre with in literature, and it is also an effective tool for embodying social life and customs within Kurdish society in all its sects. It is one of the Kurdish novels in which the lifestyle and social personality of the Kurdish characters, different levels and types, are reflected in it. The literary criticism of the school of psychoanalysis in its entirety and the theory of personal psychological analysis, in particular, of the scientist Alfred Adler is one of the most important psychological theories that paid clear attention to the personal components, which has a great relationship with the human personality, that mentions the social dimension of the human personality. As for the psychological theory for the scientist Freud, which focuses on the unconscious and the human instinct. The scientist Adler believes that the worker and the social conditions block the human interactions within society and prepare the sexual instinct for these interactions between characters. For this reason, what is meant by the psychological personality theory of the scientist Adler in the novel Khaj Al-Berlini by Hassan Ibrahim. We chose the aforementioned novel as a special sample for this study and entitled “The Embodiment of the Elements of Personal Psychological Theory of the Scientist Adler for the novel Khaj Al-Berlin by the novelist Hassan Ibrahim”, we applied the descriptive-analytical approach to this study.